Improving the Performance of Lithium‐Ion Batteries Using a Two‐Layer, Hard Carbon‐Containing Silicon Anode for Use in High‐Energy Electrodes - Gottschalk, Laura; Oertel, Christine; Strzelczyk, Nanny; Müller, Jannes; Krüger, Jannik; Haselrieder, Wolfgang; Kwade, Arno (Energy technology (Weinheim, Germany), 2023)
Lithium‐ion battery cells with high‐energy density and good fast charging properties are subject of current research. One approach to achieve high‐energy densities is the use of higher mass loadings. The challenges of these so called “thick” electrodes are transport limitations: lithium ions cannot reach all layers of the electrode, which results in a drop of performance. Possible concepts to overcome these limitations are the use of different active materials (silicon oxide, graphite, and hard carbon (HC)), and a two‐layer coating of the anode to create a defined pore network, which reduces the ionic resistance and ensure better fast charging capability even at higher mass loadings (8 mAh cm−2). It could be demonstrated that by using a two‐layered anode with HC in the upper layer, the electrical conductivity could be increased by a factor of 10 compared to the reference anode. Furthermore, the interporous HC leads to a capacity retention increase up to 20% with no loss of capacity at moderate C‐rates and a low electrode density. This can be explained by the low tortuosity that results in additional conductive paths for the ions through the coating, reduces the ionic resistance, and ultimately enables faster lithiation of the anode. In this investigation, the focus is on two‐layered anodes containing three different active materials (graphite, silicon, and hard carbon (HC)) to create a defined pore network within the anode. It could be demonstrated that the interporous HC leads to a capacity retention increase up to 20% with no loss of capacity at moderate C‐rates and a low electrode density.